Status of the Computing for Research in Africa - (:unkn) unknown (My University, 2022)
In the framework of the African Strategy for Fundamental and Applied Physics AFSAP, we have launched a survey to understand the need in computing of research scientists in Africa. In this paper we summarise the survey and extract possible guidelines and recommendations to improve the situation and boost scientific research in Africa.
Keywords: African Research